Implementation of Omnichannel Improves Business Performance Based on Integrated Marketing Communication - Siregar, Ahmad Nazri; Marsasi, Endy Gunanto (SENTRALISASI, 2024)
This research will examine a company engaged in the food and beverage industry. This research aims to create a business design based on the Business Model Canvas (BMC) approach and SWOT (Strength, Weaknesses, Opportunity, Threat) analysis as an innovation to improve the company's business performance. The object of this research is PT Tongku Raja Nauli located in Padangsidimpuan city. This research was conducted in the Micro, Small and Medium Enterprises (MSMEs) industry engaged in food processing made from egg rolls. The data collection procedure in this research is to use a qualitative approach by obtaining through direct observation, company records, in-depth interviews, and documentation in the form of photos and videos. The results of the SWOT analysis on the nine elements of the Business Model Canvas (BMC) show that there are internal and external factors that are strengths and weaknesses for the company in carrying out its business model and also what are the opportunities and threats from external that affect the business processes of PT Tongku Raja Nauli. This research resulted in the Tongku Snack Innovation program, a program that optimizes the Company's marketing. This program is assisted by Integrated Marketing Communication theory with the concept of Omnichannel Marketing which is proven to help companies increase sales, competitiveness and business continuity.